Identification and Analysis of the Novel pGAPDH-w Gene Differentially Expressed in Wild Ginseng - Han Young-Ju; Kwon Ki-Rok; Kang Won-Mo; Jeon Eun-Yi; Jang Jun-Hyeog (Korean Pharmacopuncture Institute, 2013)
Objective: Panax ginseng is one of the most medicinally used herbal medicines in the world. Wild ginseng is widely accepted to be more active than cultivated ginseng in chemoprevention. However, little has actually been reported on the differences between wild ginseng and cultivated ginseng. Method: To identify wild ginseng-specific genes, we used suppressive subtraction hybridization. Results: We report that one of the clones isolated in this screen was the GAPDH (glyceraldehyde 3-phosphate dehydrogenase) gene (designated pGAPDH-w). DNA BLAST sequence analysis revealed that this pGAPDH-w gene contained novel sequences of 94 bp. RT-PCR results showed that the expression of the pGAPDH-w gene was significantly up-regulated in the wild ginseng as compared with the cultivated ginseng. Conclusion: The pGAPDH-w gene may be one of the important markers of wild ginseng.